GAMBARAN PENGETAHUAN DAN KUALITAS HIDUP LANJUT USIA YANG MENGGUNAKAN GIGI TIRUAN DI DESA SIBUAK KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2015 - Jihan Natassa; - Zulhidriani (LPPM Universitas Muhammadiyah Riau, 2016)
The elderly must be use the denture to complete the needs of good life functionally and optimally. This research aims to determine the description of Knowledge and Life Quality Of Elderly Who Use The Denture at Sibuak Village, Tapung, Kampar In 2015. Type of this research is descriptive. The population of the elderly at Sibuak Village, Tapung, Kampar are 45 person. The sampling technique is total sampling technique. The method of data collection is questionnaire. The data is processed by a computer program and presented in frequency distribution table. Then, the results showed the most of the elderly respondents who use the denture about 60-74 years are 31 person (68.9%), the majority of female respondents are 28 person (62.2%), the majority of respondents with elementary education level are 21 person (46.7%), the majority of housewife respondents are 21 person (46.7%), the majority of GTLL denture types respondents are 23 person (51.1%), and a good level of knowledge of the majority of respondents are 23 person (51.1%), also the low quality of life respondents are 26 person (57.8%). Based on the results, the elderly should be more attention and take care for their oral cavity, they also can give the information about denture benefits to others. For sure, the dentist or dental health workers should lead the others to take care their oral cavity especially for edentolus patients, so they can reach a better life quality functionally and optimally.